(untitled) (Ibrahim Cardiac Medical Journal, 2018)
Background: Foot infections are one of the major complications of diabetes mellitus and are significant risk factors for lower extremity amputation. Providing effective antimicrobial therapy is an important component in treating these infections, which requires information about pattern of bacterial growth and their antibiotic susceptibility. This study was designed to investigate the microbial pattern of diabetic foot infections and their antibiotic susceptibility. Methodology: This prospective study was conducted in Surgery Unit 1 of Bangladesh Institute of Research and Development in Endocrine & Metabolism (BIRDEM) General Hospital, Dhaka, Bangladesh from September, 2013 to November 2016. A total 81 diabetic patients of infected chronic foot ulcer were selected on the basis of convenient sampling. Data were collected on demographic characteristics (age and sex), examination findings, bacterial involvement, its type and sensitivity pattern. Wagner’s ulcer grading system was used to classify the chronic foot ulcers Result: The age distribution of the sampled population depicted that over half [42(51.8%) out 81] of the patients was in their 5th decade of life. Females were slightly higher (53.1%) than the males (46.9%) with mean ages of the male and female patients being 48.0 ±1.5 and 53.0 ±1.2 respectively. Based on Wagner ulcer grading system, 45.7% of the foot ulcers were grade II followed by 21.0% grade III, 13.6% grade IV, another 13.6% grade I and only 6.2% grade 0. Most of the infections were polymicrobial (88.9%) and isolated micro-organisms were frequently E. coli (47.1%) and Klebsiella (33.3%). The antibiotics sensitivity against the micro-organisms demonstrated that colostin was the most sensitive antibiotics (97.5% of all cases), followed by imipenem (90.1%) and meropenem (90.1%). Conclusion: Chronic foot ulcers in diabetic patients are usually associated with polymicrobial infection. E. coli, Klebsiella and Pseudomonas are the most common micro-organisms isolated, which are sensitive to colostin, imipenem and meropenem in majority of the cases. Ibrahim Card Med J 2016; 6 (1&2): 51-55